Digital image processing algorithms and applications - Pitas, I. (Ioannis) ) (New York : Wiley, 2000)
"With the field of digital image processing rapidly expanding, there is a growing need for a book that would go beyond theory and techniques to address the underlying algorithms. Digital Image Processing Algorithms and Applications fills the gap in the field, providing scientists and engineers with a complete library of algorithms for digital image processing, coding, and analysis. Digital image transform algorithms, edge detection algorithms, and image segmentation algorithms are carefully gleaned from the literature for compatibility and a track record of acceptance in the scientific community."
"The author guides readers through all facets of the technology, supplementing the discussion with detailed lab exercises in EIKONA, his own digital image processing software, as well as useful PDF transparencies. He covers in depth filtering and enhancement, transforms, compression, edge detection, region segmentation, and shape analysis, explaining at every step the relevant theory, algorithm structure, and its use for problem solving in various applications. The availability of the lab exercises and the source code (all algorithms are presented in C-code) over the Internet makes the book an invaluable self-study guide
Digital image processing fundamentals -- Digital image transform algorithms -- Digital image filtering and enhacement -- Digital image compression -- Edge detection algorithms -- Image segmentation algorithms -- Shape description -- Digital image processing lab exercise using EIKONA
"A Wiley-Interscience publication."
Includes bibliographical references and index
1
Keywords: Algorithms; Computer algorithms; Image processing -- Digital techniques